On factors for separation of the stock of beluga whale Delphinapterus leucas in the Anadyr Gulf of the Bering Sea - Denis I. Litovka; Ludmila N. Khitzova (Известия ТИНРО)
New eco-ethological data on the Anadyr stock of beluga whales are presented based on 14-year (2000-2013) studies by methods of satellite tracking telemetry, multi-spectral aerial surveys and genetic analysis, as well as traditional and ecosystem-based approaches. Possible factors of the separate stock formation in the Anadyr Gulf are discussed, as geographic isolation, environmental conditions, foraging resources, elimination of the beluga whales, and biological isolation (on the results of genetic analysis). The beluga whales are well-adapted to oceanographic conditions and ice regime of the Arctic waters that is realized in their relationship with edge of the sea ice, ability to live in both salt and fresh waters (they enter rivers), and versatility in feeding. Their ice-associating, high sociality, and white protective coloration provide protection against killer whales and other predators and their eury-halinity allows to expand the feeding grounds both to the sea and rivers and hunt for both freshwater, anadromous and marine prey. The food spectrum of beluga whales in the Anadyr estuary is very wide and includes 12 fish species and 1 crustacean species. In the summer-autumn season, the salmons are the most significant part of the diet, as chum salmon Oncorhynchus keta , pink salmon O. gorbuscha and arctic char Salvelinus malma , whereas arctic smelt Osmerus mordax dentex , saffron cod Eleginus gracilis , sculpins Cottidae sp., anadyr whitefish Coregonus anaulorum , and siberian whitefish Coregonus sardinella are presented in the diet to a lesser extent. There is supposed on the base of episodic net surveys, that the beluga whales feeding in marine areas is more diverse, and the most important their prey in the sea are walleye pollock Theragra chalcogramma , pacific cod Gadus macrocephalus , flounders Pleuronectidae sp., sculpins Cottidae sp., capelin Mallotus villosus catervarius , polar cod Boreogadus saida , halibuts Pleuronectidae sp., stingrays Bathyraja , herring Clupeidae sp., and several species of decapod crustaceans Hyppolitidae sp. and Lithodidae sp. Natural enemies of beluga whales are killer whale Orcinus orca , polar bear Ursus maritimus , and predatory form of pacific walrus Odobenus rosmarus . Rather large number of beluga whales are eliminated by the sea ice, up to 80 animals annually, that exceeds in several times the aboriginal landings in Chukotka. Parasitic fauna of the beluga whale is still unclear and requires special investigations; the cases of epizooty are unknown in the Anadyr Gulf. Philopatry is proper to the Anadyr beluga whales, with preference of the Anadyr estuary and the Anadyr Gulf as their habitats, that is explained by optimal for them environments and high food capacity. Unique adaptation of beluga whales to the environments of the Anadyr estuary is their ultrasonic vocalization in the high-turbidity waters. Genetic analysis shows a differentiated distribution of the beluga whales haplotypes in different areas of the North Pacific, so the stock of the Anadyr Gulf is significantly isolated in the post-glacial times. Low anthropogenic pressure on beluga whales in the Anadyr Gulf allows them to maintain their stock there.